2014
DOI: 10.1371/journal.pone.0115808
|View full text |Cite
|
Sign up to set email alerts
|

Flatfoot Diagnosis by a Unique Bimodal Distribution of Footprint Index in Children

Abstract: BackgroundMore than 1000 scientific papers have been devoted to flatfoot issue. However, a bimodal distribution of flatfoot indices in school-aged children has never been discovered. The purposes of this study were to establish a new classification of flatfoot by characteristic in frequency distribution of footprint index and to endue the classification with discrepancy in physical fitness.Methods/Principal FindingsIn a longitudinal survey of physical fitness and body structure, weight bearing footprints and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
2
28
0
4
Order By: Relevance
“…It revealed that the sample size of 15 participants would be sufficient for the analysis. The static arch index for each participant was calculated as the foot width at the narrowest point divided by that at the widest point times 100% [ 8 , 24 ]. This is also called the Chippaux and Smirakarc index (CSI) developed by Chippaux and Smirakarch [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…It revealed that the sample size of 15 participants would be sufficient for the analysis. The static arch index for each participant was calculated as the foot width at the narrowest point divided by that at the widest point times 100% [ 8 , 24 ]. This is also called the Chippaux and Smirakarc index (CSI) developed by Chippaux and Smirakarch [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…(In a context of detection, a bimodal distribution may be preferable to one with just a single mode. See, for instance, [ 36 ] for a contrasting application to the explicit diagnosis of pes planus .)…”
Section: Discussionmentioning
confidence: 99%
“…Children with painful TCC and RFF (defined "Staheli Arch Index" > 1. 28 and rearfoot eversion > 10° [30,31]) were enrolled. Computed Tomography (CT) was performed to confirm the diagnosis.…”
Section: Methodsmentioning
confidence: 99%